Application of laser-induced incandescence to the investigation of soot formation in laminar diffusion flames under microgravity - Will, Stefan; et al. (30th International Symposium on Combustion, Abstracts of Works-in-Progress Poster Presentations, 2004)
Laser-induced incandescence was successfully applied to the investigation of soot formation in both buoyant and non-buoyant laminar diffusion flames. Experiments were conducted for jet-diffusion flames, where the fuel flow was provided through a tube surrounded by a concentric outer tube for an air co-flow. The fuels used were CH, ethylene, and propane. The features of soot formation and oxidation were drastically altered under microgravity. All flames were distinctively broadened, typically the heights were increased only slightly. Maximum temperatures were reduced by roughly 100-220 K under microgravity depending on the fuel. The maximum soot concentration of the non-buoyant flames strongly depended on the boundary conditions and the fuel used. The results demonstrated that laser-induced incandescence could be successfully employed for simultaneous 2-dimensional in-situ measurements of soot volume concentration and primary particle size also under microgravity conditions. This is an abstract of a paper presented at the 30th International Symposium on Combustion (Chicago, IL 7/25-30/2004).